Navigating the New Normal: Exploring How School Principal Roles Impact Teacher Competency Enhancement - Yayat Suharyat; Lusiana Lusiana; Nomin Nomin (AL-ISHLAH: Jurnal Pendidikan, 2024)
In the new normal, the education world is changing to be more challenging and interesting, including exploring the principal's role and improving the competence of teachers. This article aims to explain the principal's role relationship in improving the competence of teachers in the era of a new normal situation. In this study, we administered and collected data in three vocational schools (SMK). The data were obtained from 40 participants using the semi-structured interview, descriptive data analysis, and Chi-square analysis. The results found that the role of the principal reached 50% both as an educator and a school manager. In addition, it also increases the competence of teachers by around 40% less in the academic aspect and professional achievement to enter the era of the new normal. The chi-square analyzed the hypothesis that showed a significant relationship between the principal's role and the improvement of teachers' competence. It confirmed that the principal's role directly related to or affected the improvement of teachers' competence. In conclusion, the integration of both the principal roles and the improvement of teacher competence affect the educational program's success in the new normal situation.